On the Concept of Information - Şafak Ural (Türk Kütüphaneciliği)
These are the decrypted version of lecture notes by the guest lecturer in Istanbul University Department of Informatics for Information Management courses for postgraduates. The author takes information as the fundamental data enabling motion and discusses it within the scope of concepts such as thinking, knowing and being conscious.